Design of robust and fragile image watermarking system for copyright protection and authentication using lifting wavelet transform and bivariate empirical mode decomposition techniques - Abbas, Nidaa Hasan (2017)
In this thesis, a dual purpose watermarking system is designed that satisfy both robustness and fragility, and thus combining copyright protection and tamper proofing simultaneously without significantly degrading each other. The proposed copyright scheme is new and effective. Two transforms which are; lifting wavelet transform (LWT) and bivariate empirical mode decomposition (BEMD), are used to decompose the original image to provide flexibility in choosing the robust frequency subband of the original image. LWT, is chosen as it is fast and keeps the integrity of the retrieved watermark. While BEMD could sift the image from the most robust to the least sensitive (fragile) frequency bands. This property is exploited in this thesis to embed the watermark in the robust part of BEMD which is the residue (r). To ensure the integrity and authenticity of digital images, a wide variety of authentication schemes have been proposed in the literature to detect image tampering. However, most of the existing schemes either fail to address this issue or use inaccurate method to evaluate the system performance. For this reason, a procedure to generate a new type of fragile watermark that can detect any tampering is developed in this thesis. The most sensitive subbands of the BEMD which are Intrinsic Mode Function (IMFs) are used to derive and embed the watermark bits in the frequency domain and further processed to increase the security and the ability to detect any alteration. Another watermark is generated and embedded in the spatial domain using block wise method and the Least Significant Bits (LSBs) insertion. The dual-purpose scheme is obtained by combining both the copyright protection and image authentication schemes and has been subjected to robust and fragile attacks. The results demonstrated that the performance of the scheme remains at par or only degrade at an acceptable level after inserting the dual watermarks. The obtained visual quality, Peak Signal to Noise Ratio (PSNR), is greater than 48dB and the Normalised Cross Correlation (NCC) is greater than 0.97 while the tampering detection rate (AV) is greater than 94%.